The Whānau Rangatiratanga Frameworks: Approaching whānau wellbeing from within Te Ao Māori - Baker, Kahukore (Social Policy Evaluation and Research Unit (Superu), 2016)

Report of the Independent Monitoring Mechanism on implementation of the UN Declaration on the Rights of Indigenous Peoples in Aotearoa New Zealand: 2019 - Whare, Tracey; Charters, Claire; Ngatai, Jessica (2019)

An Exquisite Politeness: The Royal Commission on Genetic Modification and the Redefining of the Treaty of Waitangi - Jackson, Moana (2001)
Keywords: marginalisation; tiriti o waitangi/treaty of waitangi

Report of the Independent Monitoring Mechanism regarding the implementation of the UN Declaration on the Rights of Indigenous Peoples in Aotearoa New Zealand, June 2018 - Whare, Tracey; Charters, Claire; Ngatai, Jessica (2018)
Keywords: governance; iwi politics; matike mai

Homeless and landless in two generations – Averting the Māori housing disaster - Reid, John; Rout, Matthew (2019)
Keywords: economics

Te niho o te taniwha teeth of the taniwha: Exploring present-future pathways for whānau and hapū in Māori economies of wellbeing - Rout, Matthew; Spiller, Chellie; Reid, John; Mika, Jason; Haar, Jarrod (2022)
This report outlines the scope of the project He oranga whānau: mahi ngātahi Whānau livelihoods within the context of work and Māori economies of wellbeing, which has been funded by Ngā Pae o te Māramatanga—the New Zealand Māori Centre of Research Excellence. Its purpose is to set the direction and design for the research project. To say the creation of such economies will be a complex task is an understatement. Three factors make this task a ‘wicked problem’. First, the ongoing material, socio-cultural, and psychological impacts of colonisation. Second, the entwined nature of the ‘Māori economy’ within the wider settler economy, and the settler economy’s enmeshment within the global economy. Third, future uncertainty at the regional, national, and international levels in which such an economy must operate.
Keywords: not sure how to tag; wellbeing

Principles of Māori Data Sovereignty - Te Mana Raraunga (Te Mana Raraunga, 2018)
Keywords: data sovereignty; kaitiakitanga; kotahitanga; manaakitanga; rangatiratanga; tikanga | indigenous law; whakapapa; whanaungatanga

Māori Values and Perspectives to Inform Collaborative Processes and Planning for Freshwater Management. Landcare Research contract Report No. LC2119. 66p. - Robb, Mahuru; Harmsworth, Garth; Awatere, Shaun (2015)
This report was written in response to the new freshwater reforms and VMO research objectives. The initial research question to be answered was: What is the role of cultural monitoring to inform the collaborative process? This research question was broadened to “provide Māori values and perspectives that inform collaborative processes and planning for freshwater management”, and includes a section on the role of cultural monitoring in collaborative processes. Key objectives were: • Document the Māori historical and legislative context for the collaborative process, including the role of the Treaty of Waitangi • Collate case study information from around New Zealand, on co-governance, co-management and co-planning and define these terms • Provide a range of useful tools to support successful collaboration by Māori and councils in collaborative freshwater management • Identify future challenges.
Keywords: co-governance; tiriti o waitangi/treaty of waitangi; water management

The COVID 19 domestic vaccine pass: Implications for Māori - Kukutai, T.; Clark, V.; Mika, J.; Muru-Lanning, M.; Pouwhare, R.; Sterling, R.; Teague, V.; Watts, D.; Cassim, S. (National Institute of Demographic and Economic Analysis, University of Waikato, Aotearoa New Zealand, 2021)
The New Zealand government has introduced a COVID-19 domestic vaccine pass to be used in conjunction with the COVID-19 Protection Framework. The Framework is likely to be activated soon after Cabinet meets on 29 November 2021. The pass will be necessary to access places and events that require proof of vaccination under the Framework. This brief does not argue for or against the introduction of a domestic vaccine pass, but rather discusses key issues that it raises for Māori, and suggests actions to address them. We see four key issues: • the lack of Māori involvement, as a Tiriti partner, on either the design or implementation of the COVID-19 domestic vaccine pass; • disproportionate restriction on Māori mobility due to lower Māori vaccination rates; • privacy and data security concerns; • uneven implementation that could increase discrimination against Māori and other groups considered to pose a risk to others’ safety. To respond to these issues we recommend that the implementation of the pass be designed in partnership with Māori and comply with Māori data sovereignty requirements. As Tiriti partners, Māori should expect that the pass will keep their communities safe, while providing opportunities to enact manaakitanga in the matrix of care, and the mana to manage their own affairs.
Keywords: covid-19; data collection; data sovereignty; privacy; tiriti o waitangi/treaty of waitangi; treaty obligations

Governance of Māori Data - Hudson, Māui; Silveira, Tumanako (Ngā Pae o te Māramatanga, 2018)
Keywords: data; data sovereignty; indigenous data sovereignty

Submission on Water Issues in Aotearoa New Zealand - Bargh, Dr Maria (Office of the High Commissioner for Human Rights, 2007)
Keywords: government; hapū; iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

He wharemoa te rakau, ka mahue. Māori engagement with local government: knowledge, experiences, and recommendations. - Cheyne, Christine M; Tawhai, Veronica M H (2007)

Whai Rawa, Whai Mana, Whai Oranga: Creating a world-leading indigenous blue economy - Mika, Jason; Rout, Matthew; Reid, John; Bodwitch, Hekia; Gillies, Annemarie; Hikuroa, Daniel; Mackey, Leane; Awatere, Shaun; Wiremu, Fiona; Rakena, Mylene; Davies, Kate; Robertson, Natalie (2019)
Keywords: environment; hapū politics; iwi politics; kaitiakitanga; mātauranga māori

Understanding Māori Rights and Interests in Intellectual Property arising from Research and Innovation - Sterling, Rogena; Riddle, KatieLee; Brooks, Robert Tūrongo; Hudson, Maui (Te Kotahi Research Institute, 2021)
Keywords: indigenous data sovereignty; intellectual property

The future of rongoa Maori: wellbeing and sustainability. - Ahuriri-Driscoll, A.; Baker, V.; Hepi, M.; Hudson, M.; Mika, C.; Tiakiwai, S. (2008)
Rongoa Maori is a holistic system of healing that has developed out of Maori cultural traditions. It has a long history of usage and credibility among Maori, and increased interest in its revival and sustainability has prompted calls for its formalisation within the New Zealand public health system. Objective and methods The objectives of the research project were to: - Examine the contribution of rongoa Maori to indigenous wellbeing, and - Identify issues for the ongoing sustainability of traditional Maori healing in New Zealand. The research process was lead by Maori researchers in collaboration with Maori healers and stakeholders. Two literature reviews were undertaken; one to provide understanding of international developments in traditional medicine, and a second to review national policy/literature related to rongoa Maori. Four focus groups and five workshops were held with groups in five communities to explore current rongoa practice and service delivery and drivers/barriers to its ongoing utilisation. The participant groups were healers and their associates, and health and local authority stakeholders.
Keywords: hauora; health; rongoa

Intellectual Property, Mātauranga Māori - Sterling, Rogena; Riddle, KatieLee; Tūrongo Brooks, Robert; Anderson, Jane; Hudson, Maui (Te Kotahi Research Institute University of Waikato, 2021)
This literature review has been conducted to consider the various national legislation and international agreements that comprise New Zealand’s Intellectual Property Rights (IP) regime. It will evaluate if and how such legislation and agreements protect and enable Māori IP rights and interests with respect to Māori data, genomic data and mātauranga Māori. The review also identifies some mechanisms that might also enhance Māori control of these types of data. The Westminster approach of legislation in New Zealand and its approach to IP protection based on Copyrights, Patents and Trade Marks are juxtaposed against traditional Maori approaches of communally held ancestral knowledge (mātauranga) passed down through generations (whanaungatanga) based on guardianship and protection (kaitiakitanga) and the self-determination of use of such knowledge (rangatiratanga). Attempting to align tikanga concepts to the Westmionster model of law is challenging as the two share completely different notions of ownership and responsibility. Expectations of protection, to prevent misappropriation and commercialisation by non- Māori of mātauranga Māori and Māori data, extend beyond the parameters of existing IP law, creates a similar disjunct. Genomic Research generates data, some of which can be protected by IP, however researchers working with genetic/genomic data from taonga species have often failed to acknowledge the non-IP interests of Maori. As a result, Maori have taken it upon themselves to advocate for their rights to data through Māori data sovereignty discourse as well as create guidelines for culturally appropriate genomic research with explicit references to data security and management (e.g. Te Mata Ira, Te Nohonga Kaitiaki). Other extra-legal options, such as Biocultural Labelling to alert users where particular data has Māori rights and/or interests, are emerging to maintain create durable provenance data and connect next users of data with the responsible Indigenous communities. Though the intellectual property regime in New Zealand may provide some protections, there are still significant areas where the legal system does not provide sufficient protections for Māori data, taonga species and mātauranga. The UN Declaration on the Rights of Indigenous Peoples provides a framework of international support for Indigenous rights, but local government and other home-grown mechanisms are important to enable Māori governance of data. Local approaches Māori Data Sovereignty and Māori Data Governance afford Maori the opportunity to be directly involved as kaitiaki of their mātauranga and assert rangatiratanga over data and its use.
Keywords: indigenous data; intellectual property; mātauranga māori

Report of Matike Mai Aotearoa – The Independent Working Group on Constitutional Transformation (2018)
This report is the result of 252 hui between 2012 and 2015. The Working Group was established at a meeting of the Iwi Chairs’ Forum in 2010 with Terms of Reference: “To develop and implement a model for an inclusive Constitution for Aotearoa based on tikanga and kawa, He Whakaputanga o te Rangatiratanga o Niu
Keywords: constitutional transformation; iwi; matike mai

Rangatiratanga: Narratives of Racism, Resistance, and Well-being - Smith, Dr Cherryl; Tinirau, Rāwiri; Rattray-Te Mana, Helena; Moewaka Barnes, Helen; Cormack, Donna; Fitzgerald, Eljon (Whanganui: Te Atawhai o Te Ao., 2021)
Keywords: colonisation; racism; rangatiratanga; self-determination; wellbeing

Chapter 3: Ethnic group classification in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (2016)
Keywords: blood quantum; crown policy; identity; self-identification

The politics and practice of counting: Ethnicity in official statistics in Aotearoa/New Zealand - Cormack, Donna (Te Rōpū Rangahau Hauora a Eru Pōmare, 2010)
The politics and practice of counting: ethnicity in official statistics in Aotearoa/New Zealand was produced as part of a broader project funded by Te Kete Hauora, Ministry of Health to investigate issues with ethnicity data in New Zealand and the implications of these for the Māori health and disability sector. The paper is one in a series of topic-based discussion papers. It aims to summarise key literature on the measurement of the Māori population in official ethnic statistics over time as a background to the accompanying discussion papers.
Keywords: crown policy; ethnic identity; ethnicity; health; health outcomes; identity; policy; statistics